Pembuatan Video Profile Sebagai Media Promosi dan Informasi Yayasan Taman Pendidikan dan Sosial Nahdlatul Ulama Khadijah Surabaya - Ibrohim, Bobby Firman Maulana; Agustiansyah, Divandra; Almas, Nabilah Alifah; Ratna Puspita Sari (DIGICOM : Jurnal Komunikasi dan Media, 2024)
In today's digital era, a company or organization's profile plays a crucial role in building its image and reputation in the public eye. Corporate profile videos have become an effective communication tool for introducing an organization's values, mission, and vision to a wider audience. The Nahdlatul Ulama Khadijah Surabaya Foundation for Education and Social Welfare, as an institution committed to the development of education and social welfare, recognizes the importance of having an informative and engaging profile video.This profile video production project aims to provide comprehensive information about the activities, programs, and social impact generated by the Nahdlatul Ulama Khadijah Surabaya Foundation for Education and Social Welfare. The methodology employed involves a qualitative approach with data collection through interviews, observations, and analysis of the foundation's documents. Subsequently, the video production process comprises several stages, namely pre-production, production, and post-production, integrating visual communication and narrative principles. The resulting profile video is expected to increase public awareness and understanding of the role of the Nahdlatul Ulama Khadijah Surabaya Foundation for Education and Social Welfare in society. Thus, this profile video not only serves as a promotional tool but also as a means of building stronger relationships with the community and relevant stakeholders..